2014
DOI: 10.2320/matertrans.m2013425
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Hydrolysis of Aluminum Based Composites for Hydrogen Production in Pure Water

Abstract: A series of Al based composites were prepared using mechanical milling method in this paper. Effects of additives including CaO, NaCl salt and low melting point metals (Ga, In, and Sn) on the hydrolysis activity of Al based composites were evaluated in pure water. Scanning electron microscopy (SEM) and X-ray diffraction (XRD) techniques were used for the microstructure analysis of as-prepared samples and their hydrolysis products. The results showed that the addition of CaO, NaCl salt and low melting point met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 28 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…Owing to the decrease of the second phase (precipitated phase or the pitting) distributed in Al matrix, the Al reactivity is slightly reduced, causing a slight decrease in the hydrogen yield [14] . Therefore, the optimum ball milling time of 6 h derived from the result of the orthogonal test should be increased to 7 h. 1) The Ga and In elements in Al alloy, which can react with pure water, mainly exist in the forms of dissolution and precipitated phase, respectively.…”
Section: Effects Of Ball Milling Time On the Reactivity Of The Alloymentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the decrease of the second phase (precipitated phase or the pitting) distributed in Al matrix, the Al reactivity is slightly reduced, causing a slight decrease in the hydrogen yield [14] . Therefore, the optimum ball milling time of 6 h derived from the result of the orthogonal test should be increased to 7 h. 1) The Ga and In elements in Al alloy, which can react with pure water, mainly exist in the forms of dissolution and precipitated phase, respectively.…”
Section: Effects Of Ball Milling Time On the Reactivity Of The Alloymentioning
confidence: 99%
“…The shortcoming of this method is the requirement for high reaction start temperatures (more than 40 °C) and relatively low reaction rates [7,8] . In addition, the low melting point metals such as gallium (Ga) and indium (In) are also added to Al for the sake of surface activation promotion [9][10][11][12][13][14][15] . To our knowledge, no studies have been reported on the Al alloy-water reaction under low temperature conditions (0 o C).…”
mentioning
confidence: 99%
“…Hydrogen is one of the cleanest energy source with its high efficiency, zero emission, and renewability in recent years [1][2][3][4][5]. The wide use of hydrogen is a potential route to reduce the negative impact of the enormous carbon emissions caused by fossil fuels burning [5]. The lack of an efficient and safe medium for hydrogen storage and generation hindered the commercialization of fuel cell-based portable devices [6].…”
Section: Introductionmentioning
confidence: 99%
“…Described herein is an investigation into the conditions for the growth of high-purity alumina aerogel that can be accomplished using a gallium–indium–tin liquid metal alloy, that is, without the use of toxic liquid mercury and very low or no water content in the product. Many reports have recently demonstrated the capability of Ga–In–Sn and similar alloys to activate the surface of aluminum for its rapid hydrogen evolution reactions with water. However, investigations have not yet focused on the potential growth of aerogels using this alloy at room temperature. A novel process has been investigated that can function to activate aluminum contained within either pure or impure aluminum alloys, such as 7075 used for aircraft parts, for its oxidation and growth, producing a high-purity, high surface area similar to an aerogel-like material.…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have recently demonstrated the capability of Ga−In−Sn and similar alloys to activate the surface of aluminum for its rapid hydrogen evolution reactions with water. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]investigations have not yet focused on the potential growth of aerogels using this alloy at room temperature. A novel process has been investigated that can function to activate aluminum contained within either pure or impure aluminum alloys, such as 7075 used for aircraft parts, for its oxidation and growth, producing a high-purity, high surface area similar to an aerogel-like material.…”
Section: ■ Introductionmentioning
confidence: 99%